Impact of anti-sticking coating technology on shear strength at the clay-metal interface in cohesive strata - Liu, Pengfei; Sun, Shicheng; Yang, Zhao; Ji, Fuquan; Xu, Chao; Zhu, Hanbiao (Frontiers in Earth Science, 2023)
The shield machine is clogged frequently when tunneling in cohesive strata. Shield clogging is closely linked to the shear strength exhibited at the clay-metal interface. To investigate the impact of anti-sticking coating technology on the shear strength at the clay-metal interface, a series of direct shear tests were conducted. The obtained test results revealed an initial increase in shear stress at the clay-metal interface as shear displacement increased, eventually reaching a state of stabilization. The shear strength exhibited a gradual increase initially, followed by a significant increase, and eventually reached a plateau with the rise in the consistency index. It was observed that the adhesion between the anti-adhesion coating and clay was relatively weak, but the presence of the anti-adhesion coating effectively reduced the risk of shield clogging.